Pembuatan Video dan Penggunaan Youtube dalam Meningkatkan Skill, Kemampuan dan Keterampilan Mahasiswa Prodi Pkn Universitas Cenderawasih - Yan Dirk Wabiser; Sario Itlay (FKIP, Universitas Palangka Raya, 2024)
The purpose of the study was to explore the impact of video making and the use of the YouTube platform to improve the skills of students of the Civic Education Study Program (PKN) at Cenderawasih University. The method of this research is a qualitative approach, and data collection through interviews, observations, and analysis of video content produced by students. The results showed that video making not only improved students' technical skills, but also strengthened their understanding of teaching materials. In addition, the use of YouTube as a distribution medium expands audience reach and enhances interaction with the community. The findings are expected to contribute to curriculum development as well as learning methods in Civics Study Program